Titanium dioxide nanowires modified tin oxide hollow spheres for dye-sensitized solar cells. (9th September 2016) - Wang, Yajie; Fei, Chengbin; Zhang, Rong; Guo, Lixue; Shen, Ting; Tian, Jianjun; Cao, Guozhong
Abstract: Abstract : Tin oxide (SnO2 ) hollow spheres modified with titanium dioxide (TiO2 ) nanowires (NWs) synthesized by sequential hydrothermal reactions were investigated as photoanodes for dye-sensitized solar cells. Not only does the hydrothermal treatment form numerous short TiO2 NWs on the surface of SnO2 spheres, but also passivates the surface of SnO2 . Consequently, the specific surface area of the photoanode and dye loading are almost doubled, at the same time the surface defects and charge recombination are both appreciably reduced. As a result, the short-circuit photocurrent density and open-circuit photovoltage both greatly increased. The power conversion efficiency of the solar cells increases from 0.4% to 2.9%.